EEG Spectral Reaction Mapping to Binocular Flash Stimulation for Detecting Epileptic Foci and their Relation with Consciousness Disorders - Psatta, Dan Michael (Achievements and Challenges of Medicine and Medical Science Vol. 1, 2024)
Objective: The objective of the study is to find a method evidencing characteristic patterns of Epilepsy in patients with rare clinical or EEG manifestations. Methods: The present study recommends the utilization of binocular Flash stimulation (0.6 Ws, 20 sec, 1c/sec) and the EEG Spectral Reaction Mapping (SRM) for the diagnosis of Epilepsy. SRM is obtained by comparing (%) the results of partial EEG Power analysis in conditions of Flash stimulation and Rest (eyes closed). 100 epileptics and 100 non-epileptic subjects (50 normal and 50 vascular disease subjects) were put under investigation. Recordings were done with scalp electrodes in the 10-20 International System. Power analysis was made in Source Derivation. Results: This imagistic method revealed in 91% of 100 epileptics clear-cut cortical areas of enhanced excitability (Delta+Theta/Alpha+Beta coefficient increase). In change, in 50 vascular patients, the same coefficient power was decreased (t= 15.1, p< 0.0001). The difference was relatively lower considering normal EEG power values (t=6.5, p<0.001). In a lot of cases, epileptic foci activation was associated with a diminished reaction to flash of the visual occipital areas. A comparative study of the EEG SRM aspect and VEP morphology was made in order to disclose the pathologic findings. Discussion: The accurate evidence by SRM of epileptic foci is based on the development in these foci of the slow unspecific components of VEPs. Sensory areas, activated by the primary cognitive visual pathway sooner, would attract the nonspecific VEP components in their definite areas. It is considered, by comparing EEG SRMs with the average Visual Evoked Potentials (VEPs) components analysis, that highly excited epileptic foci may attract the nonspecific (reticular--limbic) activation, from the primary sensory areas generating Consciousness disorders. Conclusion: EEG SRM is a reliable method for the diagnosis of epilepsy. It is also able to reveal the origin of mental disorders associated with epilepsy.